Publisher Correction: The machineries, regulation and cellular functions of mitochondrial calcium. Issue 11 (November 2018) - Giorgi, Carlotta; Marchi, Saverio; Pinton, Paolo
In the original version of the article, sentences highlighting references 108, 137 and 175 incorrectly refer to other items in the reference list: reference 106, 132 and 169, respectively, which were corrected — in order — to reference 110, 136 and 176. The changes have been made in the HTML and PDF versions of the manuscript.